Comparative Analysis of Production and Farming Income Organic and Non-Organic Cashew in Lakudo District Central Buton Regency - Wa Nur Rahmah; Bahari, Bahari; Wa Ode Yusria (International journal of technology and education research, 2024)
This study aims to find out: The amount of production and income of organic cashew farmers and non-organic cashew farming and determine the comparison of production and income of organic cashew farmers and non-organic cashew farming in Lakudo District, Central Buton Regency. The population in the study is all farmers who cultivate organic and non-organic cashew farming in Lakudo District. Sample determination was determined by proportional stratified random sampling, the sample in this study was 49 respondents.The analysis was carried out using the concepts of income and t-test. The results of the study show that (1) The total average income of organic cashew farming is Rp.763,278/ha in one year, with an average production of 113.7 kg/year, with an average revenue of Rp.1,364,444 and an average production cost of organic cashew farming of Rp.601,167 in one year. Meanwhile, non-organic cashew farming has an average income of Rp.4,285,413/ha in one year, with an average production of 462.3 kg/year, with an average revenue of Rp.5,547,273 and an average production cost of non-organic cashew farming of Rp.2,581,487 in one year. (2) There is a significant difference between organic cashew farming income and non-organic cashew farming income, this is seen from the calculation results of the independent Sample T-test where the t-count value is 2.601>2.011 t-table, then H0 is rejected and H1 is accepted.